2021
DOI: 10.4414/smw.2021.w30083
|View full text |Cite
|
Sign up to set email alerts
|

Taxation options for nicotine and tobacco products in Switzerland – a review of tax policies

Abstract: Alternative nicotine products such as electronic nicotine delivery systems (ENDS) and tobacco heating systems have gained worldwide popularity. Findings suggest ENDS to be probably less harmful than combustible cigarettes, but evidence on long-term health effects is still lacking. The potential risk reduction by using tobacco heating systems instead of combustible cigarettes has largely been studied by tobacco industry-sponsored research. Evidence on the extent of risk reduction is key for risk-adapted taxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…If future research provides evidence that long-term use of ENDS and HTS has lower health risks than conventional cigarettes, promoting the adoption of reduced-risk products through corresponding policies could have a beneficial impact on public health. However, earlier research has shown that prices for combustible cigarettes and HTS must be increased to enable risk-based taxation as a public health goal [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If future research provides evidence that long-term use of ENDS and HTS has lower health risks than conventional cigarettes, promoting the adoption of reduced-risk products through corresponding policies could have a beneficial impact on public health. However, earlier research has shown that prices for combustible cigarettes and HTS must be increased to enable risk-based taxation as a public health goal [33].…”
Section: Discussionmentioning
confidence: 99%
“…A hypothetical upper limit of CHF 20 corresponds to current cigarette prices in the United Kingdom. However, we chose to set the upper limit even higher, at CHF 25, in consideration of Switzerland's significantly greater purchasing power [14,33]. We set the lower limit of CHF 5 below current sales prices of a pack of cigarettes.…”
Section: Dce Developmentmentioning
confidence: 99%